ECONOMIC GLOBALIZATION: HISTORICAL EXPERIENCES AND DRIVING FORCES - Hampe, Peter (Journal of European Economy, 2018)
On the basis of historical analysis it is shown that globalization has a unique history in the development of life spheres and mankind activities. At the same time, the current stage of the development is characterised by such tendencies in economic sphere that totally change the world economy. In particular, the direct foreign investment growth is greater than that of gross domestic product. The international economic exchange results in an improvement of all countries’ well-being, number of international labour division participants grows, computerisation significantly promotes international exchange reducing transportation costs. History lessons testify that globalization is not a unilateral and not irreversible process. It is more or less politically influenced and thus can be changed to a certain degree. There is made a concussing in the article that the globalization process has to be controlled in such a way that its advantages could be used for compensation to those social groups or countries that turned to become losers as a result of the process. Otherwise national or international conflicts could arise or intensify